Level evaluation of concrete dam fractures based on game theory combination weighting-normal cloud model - Li, Wei-Wei; Gu, Xin-Bao; Yang, Chao; Zhao, Chao (Frontiers in Materials, 2024)
Hazard evaluation of concrete dam fractures is vital for safe operations.The width (S1), length (S2), and depth (S3) of fractures are adopted as the assessment index, and the game theory combination weighting-normal cloud model is introduced.The normal cloud model of certain dam fractures is subsequently established. The weight coefficients of each index are calculated using game theory combination weighting, and the certainty degree of each index is determined using the cloud model.Finally, the hazard levels of the concrete dam fractures are judged. The proposed model solves the fuzziness and randomness of different indexes; the conclusions demonstrate that the model is feasible for the hazard assessment of concrete dam fractures, and its accuracy is very high; therefore, a new approach can be provided for the future hazard-level assessments of concrete dam fractures.